Relational Capital And Innovation As Drivers Of Micro Small And Medium Enterprise Sustainability: Modal Relasional Dan Inovasi Sebagai Penentu Keberlanjutan Usaha Mikro Kecil Dan Menengah - Putri, Rasti Maita; Fadliyanti, Luluk; Hak, Muhamad Bai'ul (Indonesian Journal of Innovation Studies, 2026)
General Background: MSME sustainability is increasingly shaped by the capacity to manage intangible resources and innovation within dynamic business environments. Specific Background: Intellectual capital, comprising human, structural, and relational capital, is recognized as a strategic resource for MSMEs, yet its linkage to sustainability remains underexplored when innovation is positioned as an intervening construct. Knowledge Gap: Prior studies predominantly emphasize financial performance, leaving limited empirical evidence on how intellectual capital relates to MSME sustainability measured across economic, social, and environmental dimensions. Aims: This study examines the relationships between intellectual capital components, innovation, and MSME sustainability in Indonesia, with innovation treated as an intervening variable. Results: Using SEM–PLS on data from 178 MSMEs, the findings demonstrate that relational capital shows a positive and significant relationship with innovation, while human capital and structural capital do not exhibit significant relationships. Innovation is positively and significantly associated with economic, social, and environmental sustainability dimensions. Novelty: The study introduces an integrated sustainability measurement encompassing triple-bottom-line dimensions within a single empirical model while empirically testing innovation as an intervening mechanism linking intellectual capital to sustainability. Implications: These results extend MSME sustainability literature and provide strategic insights for policymakers and practitioners to prioritize relational networks and innovation-oriented development pathways supporting long-term MSME sustainability. Highlights • Relational capital demonstrates a significant association with innovation in MSMEs• Innovation shows significant relationships with economic, social, and environmental sustainability• Sustainability is examined through an integrated triple-bottom-line empirical model Keywords Intellectual Capital; Relational Capital; Innovation; MSME Sustainability; Triple Bottom Line